Evaluation of Clinical Outcome in Traumatic Facial Nerve Paralysis - Shankar,Abhijit (2022)
Abstract Introduction The facial nerve is the most commonly paralyzed nerve in the human body, resulting in far-reaching functional, aesthetic and emotional concerns to the patient. Objective Evaluation of the clinical outcome of 47 patients with traumatic facial nerve paralyses, with respect to clinical recovery and audiological sequelae. Methods A descriptive longitudinal study was conducted over 24 months between January 2017 and December 2018 at a tertiary center with detailed clinical, topodiagnostic, audiometric and radiological evaluation and regular follow-up after discharge. Results Road traffic accidents constituted 82.98% of the trauma cases, out of which 76.60% were found to be under the influence of alcohol. Delayed facial paralysis was observed in 76.60% cases. Temporal bone fracture was reported in 89.36%, with otic capsule (OC) sparing fractures forming 91.49% of the cases. Topologically, the injury was mostly at the suprachordal region around the second genu. The majority of the patients (65%) attained full recovery of facial nerve function with conservative medical management. Audiometrically, 77.27% of the patients had hearing loss at the time of presentation, of which 64.71% were conductive in nature; 51.22% attained normal hearing at follow-up visits. Conclusion Early initiation of steroid therapy, concurrent eye care and physiotherapy are the cornerstones in the management of traumatic facial nerve paralysis.